Glue-bond performance of oil-heat-treated bamboo using cold-setting and thermosetting adhesives for engineered bamboo applications - Juanito P. Jimenez, Jr.; James Edelbert C. Ramos (Advances in Bamboo Science)
This study evaluated the glue-bond performance of cold-setting adhesives [polyvinyl acetate (PVAc) and polyurethane (PUR)] and thermosetting adhesives [urea formaldehyde (UF) and phenol formaldehyde (PF)] on giant bamboo (Dendrocalamus asper) subjected to spent cooking oil-heat treatment for engineered bamboo applications. The effects of treatment on wettability (contact angle) and bond strength were assessed, considering temperature, adhesive type, surface pairing and glue spread rate. Oil-heat treatment improved adhesive wettability while increasing the bamboo’s hydrophobicity. Among the adhesives, PUR exhibited the highest bond strength in both dry and wet conditions, meeting Philippine National Standard (PNS 2099:2015) requirements, while PF performed reliably in wet conditions. PVAc was unsuitable for wet applications. Outer-outer surface pairings enhanced bond strength, while glue spread rate had minimal impact, except for PVAc. The feasibility of oil-heat treatment in bamboo bonded with PUR was validated through prototype furniture and handicrafts, demonstrating its potential as a sustainable alternative to traditional timber for furniture and construction.